Legal basics of mineral policy in Europe an overview of 40 countries - Tiess, Gunter (Springer, 2011)
This reference covers the legal frameworks of mining of forty European countries, especially those in the southeast, which possess a large wealth of deposits. It discusses relevant legislation and offers an overview of approaches to mineral resources policy.